2023
DOI: 10.1002/glr2.12060
|View full text |Cite
|
Sign up to set email alerts
|

Functional group richness increases multifunctionality in intensively managed grasslands

Laura Argens,
Caroline Brophy,
Wolfgang W. Weisser
et al.

Abstract: BackgroundAgricultural yields have increased continuously over the last few decades. However, a focus solely on production can harm the environment. Diversification of agriculture has been suggested to increase production and sustainability. Biodiversity experiments showed positive effects on ecosystems and productivity. However, application of these results to intensively managed grasslands has been questioned due to differences in plant species and management regimes. Research on whether diversity can benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…Savage et al 9 investigated five ecosystem services (including biodiversity-and soil-related services) and management factors in three plant communities and concluded that "a single management solution to maximise the delivery of all ecosystem services is unlikely to exist, as trade-offs also occurred. " Thus our finding that no single community maximised all ecosystem functions is in broad agreement with comparable studies 6,7,9 . We found that diversity strongly affected multifunctionality; however, it was dependent on the combination of species, functional group and relative abundance.…”
Section: Diversity Increased Multifunctionality But Did Not Maximise ...supporting
confidence: 93%
See 3 more Smart Citations
“…Savage et al 9 investigated five ecosystem services (including biodiversity-and soil-related services) and management factors in three plant communities and concluded that "a single management solution to maximise the delivery of all ecosystem services is unlikely to exist, as trade-offs also occurred. " Thus our finding that no single community maximised all ecosystem functions is in broad agreement with comparable studies 6,7,9 . We found that diversity strongly affected multifunctionality; however, it was dependent on the combination of species, functional group and relative abundance.…”
Section: Diversity Increased Multifunctionality But Did Not Maximise ...supporting
confidence: 93%
“…They also showed that multifunctionality of low-nitrogen mixtures was at least as high as that in high-nitrogen grass monocultures 6 . With a similar design and the same species as in our study, Argens et al 7 investigated seven ecosystem functions (related to agronomy, biodiversity, plant physiology and soil nitrogen), and found that different species compositions promoted different individual functions; although multifunctionality increased with functional group and www.nature.com/scientificreports/ species richness, it was maximal for legume-herb combinations. Dooley et al 8 found higher performance and lower variability across three agronomic functions in four-species mixtures compared to monocultures; they found that trade-offs occurred mostly in monoculture communities.…”
Section: Diversity Increased Multifunctionality But Did Not Maximise ...mentioning
confidence: 88%
See 2 more Smart Citations